2015
DOI: 10.1111/dmcn.12838
|View full text |Cite
|
Sign up to set email alerts
|

A validation study of a modified Bouchard activity record that extends the concept of ‘uptime’ to Rett syndrome

Abstract: BARBouchard activity record SAMStepWatch activity monitor AIM The aim of this study was to investigate the validity of using a Bouchard activity record (BAR) in individuals with Rett syndrome to measure physical activity, as compared with pragmatic criterion standard measures of walking status and step counts recorded using the StepWatch activity monitor (SAM).METHOD During the waking hours of 1 day, 43 females (mean age 21y, SD 9y) wore a SAM whilst a proxy completed a modified BAR. Responses to the BAR were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Performing transition movements such as sit to stand are believed to be influenced by dyspraxia and are typically difficult in Rett syndrome, 2 although once assisted to the standing position, those who can walk will usually take steps. 21 We have previously observed that, compared with those unable to walk, maintenance of walking skills is associated with less marked progression of scoliosis. 3 Extending our understanding for those with walking skills, scoliosis had little relationship with the amount of activity.…”
Section: Discussionmentioning
confidence: 98%
“…Performing transition movements such as sit to stand are believed to be influenced by dyspraxia and are typically difficult in Rett syndrome, 2 although once assisted to the standing position, those who can walk will usually take steps. 21 We have previously observed that, compared with those unable to walk, maintenance of walking skills is associated with less marked progression of scoliosis. 3 Extending our understanding for those with walking skills, scoliosis had little relationship with the amount of activity.…”
Section: Discussionmentioning
confidence: 98%
“…There is growing recognition of the importance of physical activity for individuals with disability and clinicians are ideally placed to recommend services and support, and we have already developed measures to identify walking-based functional skill 7 and activity. 8,9 In individuals with capacity to walk, steps were accurately measured using the StepWatch Activity Monitor™ (SAM) compared with other accelerometer devices including the activPAL™. 8 Using a modified Bouchard activity record (BAR), 10 the duration of standing and walking activities or 'uptime' was strongly associated with the number of daily steps.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, researchers have developed and validated measures of gross motor capacity [11,16] and gross motor performance [15,17] which include walking. A specific measure of functional walking capacity and a brief measure of walking performance have not yet been reported in RTT.…”
Section: Introductionmentioning
confidence: 99%